Contribution of Online Media Citizen Journalism to Create City Images - Agus Triyono (FISIP Universitas Atma Jaya Yogyakarta, 2019)
Citizen journalism develops dynamically through online media. Many spaces are provided to disseminate information, including information about the potential of an area. This study aims to determine the role of citizen journalism in the city of Semarang and surrounding areas. The research method used is descriptive qualitative by analyzing data through online mass media. The objecst of this research are citizen journalism channels in the mainstream media, namely Kompasiana.com owned by Kompas.com, PasangMata.com owned by detikcom, Indonesiana.id owned by Tempo, and Rubik.okezone.com owned by Okezone. The result shows that citizen journalism contributes to the development of the image of the city of Semarang.